CircSamd4 and application thereof in preparation of medicine for treating myocardial fibrosis - TANG XIAOQIANG; CHEN YAN; KONG QIHANG; LIU XIAOJING (2024)
The invention belongs to the technical field of biological medicines, and particularly relates to circSamd4 and application thereof in preparation of a medicine for treating myocardial fibrosis. In order to screen and obtain circRNA playing a key role in the myocardial fibrosis process so as to provide a medicine for preparing myocardial fibrosis, the invention provides circSamd4, a vector for reducing circSamd4 expression, a host cell containing the vector and application of the circSamd4 in preparation of the medicine for treating myocardial fibrosis. The circSamd4 which plays a key role in the myocardial fibrosis process is found for the first time, the nucleotide sequence of the circSamd4 is shown as SEQ ID NO: 1 or SEQ ID NO: 2, and it is verified that knocking down circSamd4 expression can improve cardiac systolic function damage caused by thoracic aortic arch constriction for four weeks, relieve myocardial fibrosis, inhibit myocardial fibroblast activation and inhibit myocardial fibrosis. The compound